Syriac idiosyncrasies: theology and hermeneutics in early Syriac literature - Ruzer, Sergʹ (Jerusalem studies in religion and culture, 2010)
Aphrahat : a witness of pre-Nicene Syrian theology -- Ephrem on justice, free will and divine mercy in the story of the Fall -- Liber graduum : the heavenly garden of ascetic delights -- The cave of treasures : calvary versus earthly paradise -- Philoxenus of Mabbug : hermeneutics of incarnation -- Appendix : the old Syriac gospels : textual authority and hermeneutics